Examining Autonomy in Teaching and Job Satisfaction among Learning Facilitators - Areola, PhD HSG, Eunice Mareth Querol; Galang, Maria Urduja Concepcion (Sekolah Tinggi Manajemen IPMI, 2023)
Teaching autonomy has become an important factor in the modern context of an educational institution. Teachers are becoming more and more interactive with students, especially in managing students' educational work. A teacher's teaching style depends greatly on the environment and the decisions they can make independently. Teachers can work without restriction or fear. This study took place at a private Dominican Catholic school in the Philippines. The teachers of this educational institution are called learning facilitators because the school believes in the supporting role of teachers in the teaching and learning process. Learning facilitators can teach in their preferred method if they have enough autonomy to do so. Independence in the classroom can create more opportunities for instructors to teach lessons more expressively. In this way, instructors can enthusiastically carry out educational activities that will make students more satisfied. Student satisfaction in today's society is clearly very important. Their learning strategies are dynamic and dependent on the environment.